Geophagy among East African Chimpanzees: consumed soils provide protection from plant secondary compounds and bioavailable iron - Pebsworth, Paula A.; Hillier, Stephen; Wendler, Renate; Glahn, Ray; Ta, Chieu Anh Kim; Arnason, John T.; Young, Sera L. (Environmental geochemistry and health, 2019)
Geophagy, the intentional consumption of earth materials, has been recorded in humans and other animals. It has been hypothesized that geophagy is an adaptive behavior, and that clay minerals commonly found in eaten soil can provide protection from toxins and/or supplement micronutrients. To test these hypotheses, we monitored chimpanzee geophagy using camera traps in four permanent sites at the Budongo Forest Reserve, Uganda, from October 2015–October 2016. We also collected plants, and soil chimpanzees were observed eating. We analyzed 10 plant and 45 soil samples to characterize geophagic behavior and geophagic soil and determine (1) whether micronutrients are available from the soil under physiological conditions and if iron is bioavailable, (2) the concentration of phenolic compounds in plants, and (3) if consumed soils are able to adsorb these phenolics. Chimpanzees ate soil and drank clay-infused water containing 1:1 and 2:1 clay minerals and > 30% sand. Under physiological conditions, the soils released calcium, iron, and magnesium. In vitro Caco-2 experiments found that five times more iron was bioavailable from three of four soil samples found at the base of trees. Plant samples contained approximately 60 μg/mg gallic acid equivalent. Soil from one site contained 10 times more 2:1 clay minerals, which were better at removing phenolics present in their diet. We suggest that geophagy may provide bioavailable iron and protection from phenolics, which have increased in plants over the last 20 years. In summary, geophagy within the Sonso community is multifunctional and may be an important self-medicative behavior.